2016
DOI: 10.1063/1.4947500
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic structure, and band alignment properties at epitaxial NiO/Al2O3 heterojunction evaluated from synchrotron based X-ray techniques

Abstract: The valence band offset value of 2.3 ± 0.2 eV at epitaxial NiO/Al2O3 heterojunction is determined from photoelectron spectroscopy experiments. Pulsed laser deposited thin film of NiO on Al2O3 substrate is epitaxially grown along [111] direction with two domain structures, which are in-plane rotated by 60° with respect to each other. Observation of Pendellosung oscillations around Bragg peak confirms high interfacial and crystalline quality of NiO layer deposited on Al2O3 substrate. Surface related feature in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…While GaAs has a band gap of 1.4 eV, [ 36 ] Al 2 O 3 is an ultra‐wide band gap dielectric with reported values for the band gap ranging from 7 up to 8.8 eV. [ 35,37–39 ] Figure 2d depicts a comparison of the decay constants τ obtained by exponential curve fittings (see Figure S3) for the E 2g Raman intensity of 2.5 ± 0.3‐nm‐thick h‐BN films transferred to GaAs, SiO 2 /Si, and Al 2 O 3 substrates. In comparison with SiO 2 /Si, longer and shorter time‐decay constants are, respectively, determined when Al 2 O 3 and GaAs are employed.…”
Section: Resultsmentioning
confidence: 99%
“…While GaAs has a band gap of 1.4 eV, [ 36 ] Al 2 O 3 is an ultra‐wide band gap dielectric with reported values for the band gap ranging from 7 up to 8.8 eV. [ 35,37–39 ] Figure 2d depicts a comparison of the decay constants τ obtained by exponential curve fittings (see Figure S3) for the E 2g Raman intensity of 2.5 ± 0.3‐nm‐thick h‐BN films transferred to GaAs, SiO 2 /Si, and Al 2 O 3 substrates. In comparison with SiO 2 /Si, longer and shorter time‐decay constants are, respectively, determined when Al 2 O 3 and GaAs are employed.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method applies high-energy pulses which may cause undesirable defects in the structure, and thereby change the electronic behavior of the films. PLD has been used to deposit various binary compounds [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The prominent high‐energy characteristics near hν = 856 eV and 873 eV indicate an increase in the proportion of Ni 3+ ions 20 . Some researchers reported that the increase in the Ni 3+ ions was caused by an increase in the number of Ni vacancies 21‐23 . Therefore, Ni‐A is a highly defective nickel oxide due to Ni vacancies, as shown in Figure 2D.…”
Section: Resultsmentioning
confidence: 97%